Analysis of the Relationship Between Physical Activity Level and Disease Duration in Heart Failure Patients - Nefalensy Putri Mithakul Janah; Beti Kristinawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Heart failure is a chronic condition that affects patients' quality of life and requires long-term management. Physical activity plays a crucial role in controlling the progression of heart failure. This study aimed to analyze the relationship between physical activity levels and disease duration in heart failure patients. This study used an observational study method with a cross-sectional design in 158 heart failure patients treated at a regional general hospital in Surakarta during August 2023–August 2024. Physical activity levels were measured using the International Physical Activity Questionnaire (IPAQ), and disease duration was obtained from patient medical records. The IPAQ instrument is a standardized instrument that underwent validity and reliability tests by Craig in 2003. The results of the validity test ranged from 0.14 to 0.53, with a median value of 0.30. The reliability test results ranged from 0.34 to 0.89, with a median value of 0.80. Spearman's correlation analysis showed a significant negative relationship between physical activity levels and disease duration (r = -0.951, p < 0.05), indicating that patients with higher levels of physical activity tended to have shorter disease duration. These results demonstrate the importance of increasing physical activity in the management of heart failure patients to improve prognosis.